2009
DOI: 10.1128/cvi.00370-08
|View full text |Cite
|
Sign up to set email alerts
|

Potent Adjuvant Activity of Cationic Liposome-DNA Complexes for Genital Herpes Vaccines

Abstract: Development of a herpes simplex virus (HSV) vaccine is a priority because these infections are common. It appears that potent adjuvants will be required to augment the immune response to subunit HSV vaccines. Therefore, we evaluated cationic liposome-DNA complexes (CLDC) as an adjuvant in a mouse model of genital herpes. Using a whole-virus vaccine (HVAC), we showed that the addition of CLDC improved antibody responses compared to vaccine alone. Most important, CLDC increased survival, reduced symptoms, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…We had previously shown that CLDC improved the efficacy of the gD2 (306) vaccine while CLDC alone was not protective [16], [26]. In the experiments presented here, we compared the gD2 (306) to a further truncated form of gD2 (285)) as well as to a gD2 (285) + gB2 + gH2/gL2 and to a vaccine without gD2 (gB2 + gH2/gL2) when administered with CLDC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We had previously shown that CLDC improved the efficacy of the gD2 (306) vaccine while CLDC alone was not protective [16], [26]. In the experiments presented here, we compared the gD2 (306) to a further truncated form of gD2 (285)) as well as to a gD2 (285) + gB2 + gH2/gL2 and to a vaccine without gD2 (gB2 + gH2/gL2) when administered with CLDC.…”
Section: Resultsmentioning
confidence: 99%
“…We elected to evaluate these vaccine candidates with Cationic Lipid DNA Complexes (CLDC) as the adjuvant as we had previously shown that this adjuvant appeared to be more effective than MPL/Alum, the adjuvant used in recent clinical trials of a gD2 vaccine [3], when evaluated in mouse and guinea pig models of genital HSV-2 infection [16, 26]. The cationic liposomes facilitate endocytosis and direct delivery of the plasmid DNA to the endosomal compartment thus increasing binding of nucleic acids to endosomal toll-like receptors [27].…”
Section: Introductionmentioning
confidence: 99%
“…The cationic liposome-DNA complex containing CpG motifs (CLDC) seems to have great potential to be used for vaccines. Bernstein et al showed that the CLDC greatly improved the immunogenicity of a herpes vaccine [13]. Thus, better approaches using TLR9 agonists in combination with other devices are still appearing.…”
Section: Tlr3 and Tlr9 Agonistsmentioning
confidence: 99%
“…JVRS-100 is comprised of cationic liposome–DNA complexes (CLDC) and was developed as an adjuvant for vaccines against infectious diseases and as an immunomodulator for cancer therapy (Bernstein et al, 2009; Chang et al, 2009; Lay et al, 2009; Zaks et al, 2006). It has been demonstrated that the addition of CLDC to influenza vaccines can induce robust CD4 + Th1 response and predominant IgG2a/c antibody responses in mice (Chang et al, 2009; Dong et al, 2012; Hong et al, 2010; Lay et al, 2009).…”
Section: Introductionmentioning
confidence: 99%